Clinical case of severe ulcerative colitis against the background of salmonella infection in an adolescent (Herald of the National Children's Medical Center, 2024)
Background. The aim of this study is to describe a rare clinical case of the coexistence of ulcerative colitis and salmonella infection in an adolescent, to analyze the challenges of diagnosis and therapy, and to demonstrate the necessity of a comprehensive approach in managing such patients.Materials and methods. The study is based on clinical observation data of a 16-year-old female patient with suspected ulcerative colitis. Laboratory tests were conducted, including complete blood count, biochemical analysis, tests for Clostridium difficile, serological and bacteriological tests for salmonella detection. Instrumental methods included colonoscopy with biopsy, laparoscopy, ultrasound, and multislice computed tomography (MSCT) of the abdominal organs. Histopathological examination of biopsy samples from affected intestinal areas supported the diagnosis. Continuous monitoring of symptoms, analysis of inflammatory markers, and evaluation of the effectiveness of the prescribed therapy confirmed the coexistence of ulcerative colitis and salmonella infection and helped determine the treatment strategy.Results. The clinical observation data of a 16-year-old patient with suspected ulcerative colitis were used. Laboratory methods included complete and biochemical blood tests, tests for Clostridium difficile, and serological and bacteriological tests to detect salmonella. Instrumental diagnostics involved colonoscopy with biopsy, laparoscopy, ultrasound, and multislice computed tomography of the abdominal organs. Histopathological analysis of biopsies from the affected intestinal areas further clarified the diagnosis. Dynamic monitoring of symptoms, evaluation of inflammatory markers, and assessment of treatment efficacy confirmed the coexistence of ulcerative colitis and salmonella infection and allowed the development of an appropriate therapeutic approach.Conclusion. The coexistence of salmonellosis and ulcerative colitis is a rare clinical issue. In treating patients with inflammatory bowel disease (IBD), clinicians should be alert to the presence of intestinal infections. It is known that salmonella infection can complicate ulcerative colitis, triggering or exacerbating the condition. Such patients may rapidly decompensate, making timely and appropriate therapy essential.
Keywords: ulcerative colitis; salmonellosis; inflammatory bowel diseases; comprehensive therapy; diagnosis; adolescents; immunosuppression